Field Investigation of In-Service Performance of Concrete Bridge Decks in Pennsylvania. Issue 1 (2016) - Manafpour, Amir; Hopper, Travis; Rajabipour, Farshad; Radlińska, Aleksandra; Warn, Gordon P.; Shokouhi, Parisa; Morian, Dennis; Jahangirnejad, Shervin
The results of an expert survey and field investigation of early-age bridge deck cracking in the Commonwealth of Pennsylvania are summarized in this paper. The goal was to use field data to identify factors that contribute to or reduce early-age cracking in concrete bridge decks and to assess the effect of cracks on the long-term durability of bridge decks. First, a survey of 71 employees of the Pennsylvania Department of Transportation (DOT) was conducted to collect and document their experience with early-age cracking and its relationship to long-term deck performance. Next, inspection data from 203 bridge decks were collected and analyzed to evaluate the effect of concrete mixture proportions and properties, construction methods, and rebar type on the propensity of the bridges to experience early-age deck cracking. The Pennsylvania DOT supplied inspection data for 40 older bridge decks and initial (after construction) inspection data for 163 new bridge decks. The results suggest that limiting the total cementitious materials content (e.g., to 620 lb/yd 3 ) and the maximum compressive strength (e.g., to 5, 000 pounds per square inch at 28 days) is advisable to reduce deck cracking. In addition, epoxy-coated rebar showed good corrosion resistance, even in cracked concrete.